PENGARUH GLOBALISASI INFORMASI TERHADAP KEHIDUPAN SOSIAL BUDAYA GENERASI MUDA ( SUATU STUDI DI SMA NEGERI 1 BEO KABUPATEN KEPULAUAN TALAUD ) - WABAA, MARTHA; LALOMA, ALDEN; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2014)
The population in the Talaud Islands, particularly in Beo nearly 90% are Christians.All people always respect one another. They always obey and follow the rules and / or norms, customsand respect among religions. This is reflected in the activities they do every day. Judging from thepeople who so respect the rules and customs applicable in everyday life, the inclusion of theglobalization of information and communication within a community of people who live in Beo,especially for the younger generation can cause a variety of problems, especially in the socio-culturalfield.Therefore the purpose of this study is to analyze the extent to which the impact ofglobalization of information on social and cultural life of the younger generation. This study took placein senior high school (SMA Negeri) 1 Beo Kepulauan Talaud. Design research is a quantitative studywith a sample of 60 respondents / students.The results showed that the opinions of students at SMAN 1 Beo Talaud information aboutthe impact of globalization, the average is still in the category of "medium" or moderate, which isequal to 58.33% of the 60 respondents / students, which is categorized as "low" assessment by 11respondents or 18:33% and categorized as "high" is only 23.34%. As for the social and cultural life,the average is also in the category of "moderate" that is equal to 50%, which is categorized as "low"and categorized as "high" the same judgment that each of 15 respondents, or 25%.Based on the research results, it can be stated that the globalization of information turns outto have a significant impact on social and cultural life of the younger generation.Keywords : Information Globalization, Cultur and Social, Young Generation